Evaluating Rural Health Disparities in Colombia: Identifying Barriers and Strategies to Advancing Refugee Health (2023)
ABSTRACT: Health disparities within rural communities, notably those affecting migrant and refugee populations, are well-documented. Refugees often grapple with high disease burdens and mortality rates due to limited access to primary healthcare and their vulnerable socio-economic and political situations. This issue is particularly acute in the rural areas around Medellin, Colombia, where the refugee influx exacerbates the existing public health challenges. Studies highlight a substantial gap between community needs and public health policies, resulting in inadequate healthcare access. Our study, utilizing the Delphi technique, aimed to identify common barriers and strategies to enhance rural healthcare for refugees. Through consensus-building with community leaders, we identified six primary barriers to healthcare access and five barriers to healthcare quality. Community leaders endorsed five strategies to address the access barriers and eight strategies to improve healthcare quality. This research provides valuable insights for optimizing resource allocation and designing effective support programs for these vulnerable populations.